Strategi dan Struktur Bisnis Internasional - Fatya Ayu Priasti; Nabila Dwi Afifah Lubis; Bagas Elwi Nibra; Nur Azizah; Nabila Addiva; Feronica Simanjorang (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Global trade is very important for a country and its businesses because it drives economic growth by creating markets for its products and access to needed resources. Therefore, companies that run their business worldwide must consider cultural aspects, so that corporate cultural aspects can form the basis of marketing activities. The goal of international business strategy is to gain and maintain a competitive advantage, namely a unique and advantageous competitive position in the country and in the world.